PROSPECTS FOR ALLEVIATING POVERTY AND PROTECTING THE TAUNSA BARRAGE WILDLIFE SANCTUARY, INDUS RIVER, PAKISTAN, THROUGH CULTURAL- AND ECO-TOURISM - Z. Ali; S. Y. Shelly; F. Bibi; Z. A. Nasir; I. Colbeck J. R. A. Butler (Journal of Animal and Plant Sciences, 2015)
The common assumption about protected areas is that they aggravate poverty amongst local residents by excluding them from livelihood activities such as fishing, agriculture, tourism and logging. It has been increasingly recognized that protected areas should instead contribute to sustaining the resident communities of surrounding areas. Eco-tourism could be an alternative form of income generation and has a substantial potential to boost and develop a relationship between people and nature. At the Taunsa Barrage Wildlife Sanctuary (TBWS), on the Indus River, Pakistan, local communities rely on local ecosystem services for up to 90% of their daily needs. To determine the potential for eco-tourism growth a SWOT analysis (Strengths, weaknesses, opportunities and threats) was designed based on discussion with stake holders (including community representative, non-governmental and governmental agencies)and personal observation during 2010. It is proposed as an approach for communities to utilize otherwise marginal cultural or ecological assets. Sustainability and involvement are both fundamental for the enduring future of this form of tourism. This study indicates that the prospects of eco-tourism as an instrument for empowerment and poverty alleviation at the TBWS are good. Eco- cultural tourism can offers ways to achieve sustainable resource and to engage with wider society. It could also act as a model for how cultural- and eco-tourism could empower local people in comparable settings in Pakistan. thatch and timber, recreation and tourism can be valued,
Keywords: Ecotourism; SWOT Analysis; Taunsa Barrage Wildlife Sanctuary; Pakistan